Development and test of 2.45 GHz microwave ion source based intense ion beam experimental facility. (February 2016) - Kumar, Narender; Rodrigues, G.; Mathur, Y.; Ojha, S.; Ahuja, R.; Kanjilal, D.
Abstract: An intense low energy ion beam facility has been designed, developed at Inter University Accelerator Centre (IUAC), New Delhi. This facility comprises of a 2.45 GHz microwave ion source, multi-electrode extraction system and an experimental chamber. The facility was designed to perform experiments using intense ion beams having energy in range of a few keV to a few tens of keV. The plasma chamber was designed keeping two additional ports for plasma diagnostics. In order to deliver intense ion beams on the target with low electric field, a four-electrode extraction system has been developed. This facility has been used for 10 keV N + & O + ion implantation in silicon at varying doses. The implanted samples have been characterized by using Rutherford Back Scattering (RBS), RBS Channeling (RBS-C) and Nuclear Resonance Analysis (NRA). Highlights: An intense, low energy ion beam facility at IUAC. Consists of microwave ion source, multi-electrode extraction system and experimental chamber. Used for ion implantation. Samples characterized by RBS, RBS-C and NRA.